Teaching character education to socially alienated children through puppetry primary level - Fonacier, Arcenia O. 1936-; Adorio, Mercedes P. (1973.)
The study proposed activities for character education for the socially-alienated children with the use of puppets. The study aims to know the goals of character education to socially-alienated children, th methods by which puppetry can be used as a means to achieve the goals in character education for the socially-alienated, and the activities in character education for the socially-alienated. This paper is accomplished along the research training scheme.
Vita.
Thesis (Master of Arts in Teaching - Special Education : Behavior Problem)--University of the Philippines, Diliman.
Keywords: Moral education -- Philippines; Children with social disabilities -- Education (Primary) -- Philippines; Puppet theater in education -- Philippines; Behavior modification; Alienation (Social psychology).